437 NaturSafe® increases volatile fatty acid production across various beef diets in vitro. (10th April 2018) - Butler, J M; Kwan, T; Reedy, C; Werner, T; Belknap, C R; Yoon, I
Abstract: NaturSafe is a natural nutritional health product used in beef rations to promote rumen and overall digestive health as well as balanced immunity. Previous studies have demonstrated NaturSafe's ability to replace monensin, tylosin, and direct-fed microbials in conventional beef feedlot diets with similar effects on growth performance and feed conversion, while numerically reducing liver abscess prevalence and significantly decreasing pathogen shedding and Salmonella accumulation in lymph nodes. Here we investigated the effect of NaturSafe, a Saccharomyces cerevisiae fermentation product, on in vitro volatile fatty acid (VFA) production across various beef feedlot and backgrounding diets. Five diets—backgrounder (BG ), Midwest finisher (MW ), high by-product finisher (HBP ), whole shelled corn finisher (WSC ), and steam flaked corn finisher (SFC )—were collected from multiple US feedlots. A sixth diet was created by adding tylosin (9 g/ton) to the steam-flaked corn finisher. All diets contained monensin (24-31 g/ton). Serum bottles (100 ml) containing 0.3 g of diet and treatment (Control or NaturSafe) were inoculated with buffered rumen fluid and incubated for 12 h. NaturSafe inclusion was based on a feeding rate of 18 g/hd/d. The experiment was completed with ten replicates per diet and treatment combination. Data were analyzed using the GLM model of JMP. Significance was defined as P ≤ 0.05. For Control treatments, production of acetate ranged from 19 to 21 mM; propionate from 10 to 13 mM; butyrate from 3 to 4 mM; and total VFA from 35 to 39 mM. Diets supplemented with NaturSafe resulted in acetate, propionate, butyrate, and total VFA concentrations ranging from 22 to 26 mM, 17 to 20 mM, 4 to 5 mM, and 45 to 50 mM, respectively. NaturSafe significantly increased ( P ≤ 0.01) acetate (11.5 to 17.1%), propionate (46.4 to 90.9%), butyrate (11.3 to 17.4%) and total VFA (25.0 to 38.3%) over Control on all diets tested. Results showed NaturSafe is able to enhance rumen microbial VFA production across a wide range of beef diets in vitro. Results also suggested that NaturSafe supports rumen microbial fermentation in the presence of monensin and tylosin. NaturSafe is a natural nutritional health product used in beef rations to promote rumen and overall digestive health as well as balanced immunity. Previous studies have demonstrated NaturSafe's ability to replace monensin, tylosin, and direct-fed microbials in conventional beef feedlot diets with similar effects on growth performance and feed conversion, while numerically reducing liver abscess prevalence and significantly decreasing pathogen shedding and Salmonella accumulation in lymph nodes. Here we investigated the effect of NaturSafe, a Saccharomyces cerevisiae fermentation product, on in vitro volatile fatty acid (VFA) production across various beef feedlot and backgrounding diets. Five diets—backgrounder (BG ), Midwest finisher (MW ), high by-product finisher (HBP ), whole shelled corn finisher (WSC ), and steam flaked corn finisher (SFC )—were collected from multiple US feedlots. A sixth diet was created by adding tylosin (9 g/ton) to the steam-flaked corn finisher. All diets contained monensin (24-31 g/ton). Serum bottles (100 ml) containing 0.3 g of diet and treatment (Control or NaturSafe) were inoculated with buffered rumen fluid and incubated for 12 h. NaturSafe inclusion was based on a feeding rate of 18 g/hd/d. The experiment was completed with ten replicates per diet and treatment combination. Data were analyzed using the GLM model of JMP. Significance was defined as P ≤ 0.05. For Control treatments, production of acetate ranged from 19 to 21 mM; propionate from 10 to 13 mM; butyrate from 3 to 4 mM; and total VFA from 35 to 39 mM. Diets supplemented with NaturSafe resulted in acetate, propionate, butyrate, and total VFA concentrations ranging from 22 to 26 mM, 17 to 20 mM, 4 to 5 mM, and 45 to 50 mM, respectively. NaturSafe significantly increased ( P ≤ 0.01) acetate (11.5 to 17.1%), propionate (46.4 to 90.9%), butyrate (11.3 to 17.4%) and total VFA (25.0 to 38.3%) over Control on all diets tested. Results showed NaturSafe is able to enhance rumen microbial VFA production across a wide range of beef diets in vitro. Results also suggested that NaturSafe supports rumen microbial fermentation in the presence of monensin and tylosin.